Rectal bleeding and polyps. Issue 1 (July 1993) - Latt, T T; Nicholl, R; Domizio, P; Walker-Smith, J A; Williams, C B
Abstract : Colorectal polyps are an important albeit uncommon cause of rectal bleeding in children. Colonoscopy promotes both rapid and accurate diagnosis and the opportunity for immediate therapeutic polypectomy. A 10 year audit of polyps diagnosed and treated endoscopically has been undertaken in the children's endoscopy unit. Twenty nine polyps were diagnosed from 730 colonoscopies; 24 were juvenile, two inflammatory, two Peutz-Jeghers, and one an adenomatous polyp. All but one of the juvenile polyps were solitary. All children had bleeding per rectum as one of the major presenting features. About two thirds of the patients were under the age of 5 years; the mean age was 5.6 years. Most of the juvenile polyps were on the left side of the colon; 41% were distal to the sigmoid colon. However polyps were found throughout the colon, indicating that total colonoscopy is wise and rewarding in any child with persistent and intermittent rectal bleeding.